Ultraestructura del espermatozoide de rata (Ratus norvegicus). Aplicación de tres técnicas para Microscopía Electrónica de Transmisión - Ureña, Francisco; Akahori, Hiroshi; Azofeifa, Alfredo (Revista de Biología Tropical, 1987)
Ultrastructures spermatozoa taken from the seminiferous tubules of rat testes (Rattus norvegicus) were observed under transmission electron microscopy, u sing the techniques of ultrathin sections, microspeading specimens and replicas. The heads of isolated spermatozoa were of homogeneously high electron density, and had a slightly curved end; in longitudinal sections these zones were composed of a compact homogeneous DNA, covered by a nuclear envelop, cell membrane and small amounts of acrosomal material. The middle piece contained the modified centriols in the junction zone and flagelal microtubules. In transverse sections as well as in replicas, this region consisted of 10 pairs of microtubules and 9 dense fibers surrounded circularly by the mitochondria (mitochondrial sheath).